Is there a quicker way?

Algebra Level 4

1 2 1 2 24 + 288 + 2 2 2 2 48 + 288 + + 2 3 2 2 3 2 23 ( 24 ) + 288 + 2 4 2 2 4 2 24 ( 24 ) + 288 = ? \dfrac{1^2}{1^2-24+288} + \dfrac{2^2}{2^2-48+288} + \cdots + \dfrac{23^2}{23^2-23(24)+288} + \dfrac{24^2}{24^2-24(24)+288} = \, ?


The answer is 25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ralph Macarasig
Aug 14, 2016

For each positive integer n n ,

n 2 n 2 24 n + 288 + ( 24 n ) 2 ( 24 n ) 2 24 ( 24 n ) + 288 \frac{n^2}{n^2-24n+288} + \frac{(24-n)^2}{(24-n)^2-24(24-n)+288}

= 2 n 2 2 n 2 48 n + 576 + 2 ( 24 n ) 2 2 ( 24 n ) 2 48 ( 24 n ) + 576 =\frac{2n^2}{2n^2-48n+576} + \frac{2(24-n)^2}{2(24-n)^2-48(24-n)+576}

= 2 n 2 n 2 + ( 24 n ) 2 + 2 ( 24 n ) 2 ( 24 n ) 2 + n 2 = 2 =\frac{2n^2}{n^2+(24-n)^2} + \frac{2(24-n)^2}{(24-n)^2+n^2} = 2

Then,

1 2 1 2 24 + 288 + 2 2 2 2 48 + 288 + . . . + 2 3 2 2 3 2 23 ( 24 ) + 288 + 2 4 2 2 4 2 24 ( 24 ) + 288 \frac{1^2}{1^2-24+288} + \frac{2^2}{2^2-48+288} + ... + \frac{23^2}{23^2-23(24)+288} + \frac{24^2}{24^2-24(24)+288}

= ( 1 2 1 2 24 + 288 + 2 3 2 2 3 2 23 ( 24 ) + 288 ) + ( 2 2 2 2 48 + 288 + 2 2 2 2 2 2 22 ( 24 ) + 288 ) + . . . + ( 1 1 2 1 1 2 11 ( 24 ) + 288 + 1 3 2 1 3 2 13 ( 24 ) + 288 ) + 1 2 2 1 2 2 12 ( 24 ) + 288 + 2 4 2 2 4 2 24 ( 24 ) + 288 = (\frac{1^2}{1^2-24+288} + \frac{23^2}{23^2-23(24)+288}) + (\frac{2^2}{2^2-48+288} + \frac{22^2}{22^2-22(24)+288}) + ... + ( \frac{11^2}{11^2-11(24)+288} + \frac{13^2}{13^2-13(24)+288}) + \frac{12^2}{12^2-12(24)+288} + \frac{24^2}{24^2-24(24)+288}

= 11 ( 2 ) + 1 + 2 =11(2) + 1 + 2

= 25 =\boxed{25}

Chew-Seong Cheong
Aug 15, 2016

The n n th term a n = n 2 n 2 24 n + 288 = n 2 ( n 12 ) 2 + 144 a_n = \dfrac {n^2}{n^2 - 24n + 288} = \dfrac {n^2}{(n - 12)^2 + 144}

For n < 12 n<12 , adding n n th and ( 24 n ) (24-n) th terms together:

a n + a 24 n = n 2 ( 12 n ) 2 + 144 + ( 24 n ) 2 ( 24 n 12 ) 2 + 144 = n 2 ( 12 n ) 2 + 144 + n 2 48 n + 576 ( 12 n ) 2 + 144 = 2 ( n 2 24 n + 288 ) n 2 24 n + 288 = 2 \begin{aligned} a_n + a_{24-n} & = \frac {n^2}{(12-n)^2 + 144} + \frac {(24-n)^2}{(24-n-12)^2 + 144} \\ & = \frac {n^2}{(12-n)^2 + 144} + \frac {n^2 - 48n + 576}{(12-n)^2 + 144} \\ & = \frac {2(n^2-24n+288)}{n^2 - 24n + 288} \\ & = 2 \end{aligned}

S = a 1 + a 2 + a 3 + . . . + a 24 = ( a 1 + a 23 ) + ( a 2 + a 22 ) + . . . + ( a 11 + a 13 ) + a 12 + a 24 = 11 ( 2 ) + 1 2 2 0 2 + 144 + 2 4 2 1 2 2 + 144 = 22 + 1 + 2 = 25 \begin{aligned} S & = a_1+a_2+a_3 + ... + a_{24} \\ & = \color{#3D99F6}{(a_1+a_{23}) + (a_2+a_{22}) + ... + (a_{11}+a_{13})} + a_{12} + a_{24} \\ & = \color{#3D99F6}{11(2)} + \frac {12^2}{0^2+144} + \frac {24^2}{12^2+144} \\ & = 22 + 1 + 2 \\ & = \boxed{25} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...